PENGARUH KOMUNIKASI PEMASARAN DAN MOTIVASI KONSUMEN TERHADAP KEPUTUSAN SISWA UNTUK KULIAH DI AKADEMI KOMUNITAS DHARMA BHAKTI BANGKA - Burhanudin Bani; Dedi Susanto (LPPM STIE PERTIBA Pangkalpinang, 2019)
The development of their service sectors plays a very important role in the competitive world of the service business. The companies engaged in the service sector each try to improve the quality of their service, in order to survive and develop their business. Service quality in the service industry sector plays a major role in customer satisfaction, customer retention, word of mouth communication, repurchase, loyalty, market share, and profitability. This research was intended to analyze the effect of marketing communication and consumer motivation on college the decision at Dharma Bhakti Bangka Community Academy. The population is students of MAN 1 Sungailiat Bangka Regency, a sample of 62 students. Measurement of research variables with instruments in questionnaires quantified by Likert scale. Analysis method using multiple regression analysis. Hypothesis testing uses the t-test. The results of this research are that marketing communication and consumer motivation have a positive and significant effect on the decision to study at the Dharma Bhakti Bangka Community Academy. The recommendation if this research is that the institution is expected to be able to conduct effective marketing communication and in the motivation of consumers to adjust to the consideration of market segmentation and product positioning offered